Temporary agency work - Susan N. Houseman (IZA World of Labor, 2014)
Temporary agency work has expanded in most advanced economies since the 1990s, but its growth has been controversial. Some argue that these jobs offer experience and contact with potential employers, serving as a path to regular employment, particularly for low-skilled workers. Others view them as traps, fostering low-wage, unstable employment and providing little experience and few contacts.
Keywords: 330; temporary work agencies; temporary help employment; unemployment; earnings; low-skilled workers